2021
DOI: 10.1002/cbdv.202100139
|View full text |Cite
|
Sign up to set email alerts
|

Shengxuening Extracted from Silkworm Excrement Mitigates Myelosuppression via SCF‐Mediated JAK2/STAT3 Signaling

Abstract: Shengxuening (SXN) is a Chinese patent medicine with main ingredients (including chlorophyll derivatives and sodium iron chlorophyllin) extracted from silkworm excrement. SXN exhibited efficacy in clinical trials of renal anemia and iron deficiency anemia; however, the specific mechanisms remain unclear. This study found that SXN increased the number of peripheral blood cells and improved the bone marrow morphology in myelosuppressed mouse model, reversed the reduction in body weight and spleen indices, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that SXN increased the synthesis of erythropoietin in rats, thereby ameliorating renal anemia in the animals ( Mei et al, 2021 ). Furthermore, SXN promoted the restoration of hemopoietic function in models of myelosuppression by enhancing the secretion of hematopoietic factors and activating the JAK2/STAT3 pathway ( Ding et al, 2021 ). Moreover, another study reported that SXN could also significantly upregulate the expression of granulocyte macrophage colony stimulating factor and stem cell factor in bone marrow cells, thereby alleviating cyclophosphamide-mediated myelosuppression ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that SXN increased the synthesis of erythropoietin in rats, thereby ameliorating renal anemia in the animals ( Mei et al, 2021 ). Furthermore, SXN promoted the restoration of hemopoietic function in models of myelosuppression by enhancing the secretion of hematopoietic factors and activating the JAK2/STAT3 pathway ( Ding et al, 2021 ). Moreover, another study reported that SXN could also significantly upregulate the expression of granulocyte macrophage colony stimulating factor and stem cell factor in bone marrow cells, thereby alleviating cyclophosphamide-mediated myelosuppression ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that Shengxuening attenuates myelosuppression, increases bone marrow CFU-E and CFU-GM production, increases reticulocyte percentage, and restores hematopoiesis in a hemorrhagic anemia model through the stem cell factor-mediated JAK2/STAT3 signaling pathway [20,31].…”
Section: Discussionmentioning
confidence: 99%
“…17 Silkworm excrement is a typical waste product of the mulberry industry, and the active ingredient contains a considerable amount of chlorophyll derivatives. 18,19 Although photodynamic studies of silkworm excrement were rarely performed, researchers had reported the photodynamic behavior of chlorophyll derivatives extracted from other substances. For example, PAA hydrogels containing seaweed extracts and F127 micelles encapsulating chlorophyll derived from green vegetables both exhibited vigorous photodynamic activity and photostability.…”
Section: Introductionmentioning
confidence: 99%